Body, sexuality, and gender - Naguschewski, Dirk; Veit-Wild, Flora, 1947- (Matatu, 2005)
Literary representations of the body from Africa as well as narrative strategies of writing the body have only recently begun to receive wider critical attention. The reflections on body, sexuality, and gender in African literary texts brought together in this volume do not consider these three terms as separate entities but instead as closely related to each other, each term questioning the other: bodies and sexualities that are transgressing concepts of gender, gender that is probing body and sexuality. With regard to Africa, the three concepts form a particularly contested space, because bo.